Transformation of corporate scope in U.S. banks: Patterns and performance implications - Nicola Cetorelli; Michael G. Jacobides; Samuel Stern (Federal Reserve Bank of New York, 2017)
Using a novel database containing the time-series details of the organizational structure of individual bank holding companies, this paper presents the first population-wide study of the transformation in business scope of U.S. banks. Expanding scope has a negative impact on performance on average. However, we find that firms whose expansion keeps them closer to the prevailing "modal bank" are better off compared with those pursuing generic diversification. Moreover, we find that early expanders into particular activities benefit more, whereas late adopters, rather than benefitting by "fitting the norm", lose out.
Keywords: G21; L22; L25; 330; business scope; performance; diversification